Beagles & Ramsay : New Meat. - Austin, Catherine; Ellis, Patricia; Firth, Hannah; Exhibition. Beagles & Ramsay : New Meat. Chapter Cardiff. 2004-06-12. 2004-07-25 (Cardiff : Chapter Cardiff, 2004)
Beagles & Ramsay are best known for their elaborate and theatrical installations which involve video, sculpture, photography and performance. Over the past seven years these installations have often centred on a number of adopted alter egos and mutated self-portraits, and New Meat, features specially commissioned works that develop this longstanding preoccupation. The duo has created a further series of doppelgangers possessed with a horrific beauty and mordant humour.
ind. tent., gr. tent. p. 22
Engels
boek
Keywords: Beagles & Ramsay